A MORPHOLOGICAL AND LEXICAL STUDYON PAPUAN INDONESIAN DIALECT - PANDITA AP, YOHANES (Jurnal Ilmiah Mahasiswa FIB, 2013)
Dialect is a variety of language that has uniqueness in phonology,morphology, syntax and vocabulary. One of the examples of dialect spoken inIndonesia is Papuan dialect. The uniqueness of Papuan Indonesian dialect can beseen in its morphology and vocabulary. Thus, this study was conducted to analyzethe word formation process and the lexical variation in Papuan Indonesian dialect. This study was a qualitative research. The data of this study were theutterances which contained linguistics items that mark the characteristics oruniqueness of Papuan Indonesian dialect. In doing the observation, the writer tooknotes on the relevant data from the subjects that contain morphological and lexicalvariation of PID utterances that are different from Standard BI. In data analysis,the writer classified  the data in form of table and gave further explanationaccording to the word formation processes.  The results of this study showed that there are seven word formationprocesses in the lexical variation of Papuan Indonesian dialect. They areborrowing, blending, coinage, compounding, clipping, conversion, and derivation.Coinage is the most dominant with twenty six words, followed by clipping with 7words, 6 compounding  words, 4 conversion words, 3 blending word, 2 derivation,and the last is borrowing with 1 word. In conclusion, Papuan Indonesian dialect is a Bahasa Indonesia that isspoken by Papuan. It has uniqueness in the word formation process of some of thewords. There are words that are formed differently with standard BI. Based onYule’s theory of word formation process, the writer found seven of them in PID.For further research on PID, the writer suggests to the next writer who isinterested in Papuan Indonesian dialect to analyze it from the syntax andsociolingusitics point of view. Keywords: Dialect, Papuan Indonesian Dialect, Word Formation Process.